2011
DOI: 10.1128/jcm.01965-10
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Epidemiology of Streptococcus pseudoporcinus in the Genital Tract

Abstract: Streptococcus pseudoporcinus, a beta-hemolytic microorganism first isolated from the female gastrourinary tract in 2006, cross-reacts with serogrouping kits for group B Streptococcus (GBS) and could be misidentified in the laboratory. The epidemiologic characteristics of this species have not been reported previously, but this organism is thought to be rare. Paired vaginal and rectal samples were collected from 663 nonpregnant women enrolled in a phase II clinical vaccine trial of a GBS type III capsular polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Like S. agalactiae, S. pseudoporcinus produces large colonies (typically Ͼ0.5 mm) after 24 h of incubation (which is useful for differentiating beta-hemolytic streptococci prior to Lancefield antigen typing because it excludes the possibility of beta-hemolytic strains of members of the Streptococcus anginosus group, whose colonies are characteristically smaller [Յ0.5 mm]), is CAMP factor positive, and is bacitracin resistant, and both species are most commonly isolated from the female genitourinary tract (1, 2). Although, unlike S. agalactiae, S. pseudoporcinus does not contain Lancefield group B antigen, it cross-reacts with group B antigen agglutination reagents in Streptococcus serogrouping kits (1,(4)(5)(6)(7)(8). Furthermore, colonies of S. pseudoporcinus have been reported as indistinguishable from those of S. agalactiae when chromogenic agars designed for the detection of S. agalactiae are utilized (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Like S. agalactiae, S. pseudoporcinus produces large colonies (typically Ͼ0.5 mm) after 24 h of incubation (which is useful for differentiating beta-hemolytic streptococci prior to Lancefield antigen typing because it excludes the possibility of beta-hemolytic strains of members of the Streptococcus anginosus group, whose colonies are characteristically smaller [Յ0.5 mm]), is CAMP factor positive, and is bacitracin resistant, and both species are most commonly isolated from the female genitourinary tract (1, 2). Although, unlike S. agalactiae, S. pseudoporcinus does not contain Lancefield group B antigen, it cross-reacts with group B antigen agglutination reagents in Streptococcus serogrouping kits (1,(4)(5)(6)(7)(8). Furthermore, colonies of S. pseudoporcinus have been reported as indistinguishable from those of S. agalactiae when chromogenic agars designed for the detection of S. agalactiae are utilized (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although, unlike S. agalactiae, S. pseudoporcinus does not contain Lancefield group B antigen, it cross-reacts with group B antigen agglutination reagents in Streptococcus serogrouping kits (1,(4)(5)(6)(7)(8). Furthermore, colonies of S. pseudoporcinus have been reported as indistinguishable from those of S. agalactiae when chromogenic agars designed for the detection of S. agalactiae are utilized (6). Taken together, this can make differentiation between S. pseudoporcinus and S. agalactiae difficult and has probably led to an underestimation of the former's role and frequency in human colonization and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence and clinical significance of genitourinary S. pseudoporcinus and its relationship to peripartum neonatal and maternal infections are not currently known (2,3). In 2011, Stoner et al (4) sought to identify the prevalence and epidemiology of S. pseudoporcinus in the genital tracts of nonpregnant women. They found that 5.4% of the women in their study had genital cultures positive for this bacterium.…”
mentioning
confidence: 99%